Tuberculosis and COVID-19 co-infection in Serbia: Pandemic challenge in a low-burden country - Adzic-Vukicevic, Tatjana; Stosic, Maja; Antonijevic, Gordana; Jevtic, Miroslav; Radovanovic-Spurnic, Aleksandra; Velickovic, Jelena (Frontiers in Medicine, 2022)
Introduction COVID-19 and tuberculosis (TB) represent global threats to the public health system. The impact of COVID-19 on TB results in a reduction in the number of notified TB cases, delayed diagnosis and treatment, and increased case fatality and mortality rates. The aim of the study was to analyze the TB/COVID-19 co-infected cohort in Serbia as a low-burden country and compare it to the global TB/COVID-19 cohort. Methods A retrospective analysis was done on 53 TB and COVID-19 co-infected patients treated in COVID hospital “Batajnica” in Belgrade and Special Hospital for Pulmonary Diseases “Ozren” Sokobanja in the period from 6 March 2020 to 1 April 2022. A comparative analysis with the global cohort published recently was also performed. Results TB/COVID-19 cohort in Serbia included significantly fewer migrants and diabetes cases, but more cases with chronic respiratory diseases compared to the global. Descriptive analysis of TB cases in the Serbian TB/COVID-19 cohort showed fewer cases diagnosed with sputum smear and Gene Xpert/HAIN, fewer EPTB and mono-resistant cases, and more cases diagnosed with solid culture, unilateral pulmonary infiltrate (with bilateral cavity lesions), and bilateral pulmonary infiltrate (no cavities) compared to TB/COVID-19 cases worldwide. Nasal congestion and fever were more common COVID-19 symptoms in the global cohort. Radiology was more commonly used for the diagnosis of COVID-19 in Serbia. Typical bilateral ground opacities were less common among Serbian patients. Serbian patients spent fewer days in the hospital and achieved a higher PCR conversion rate and TB treatment success rate. Conclusion The Serbian TB/COVID-19 cohort achieved a higher treatment success rate compared to the global cohort. Encouraging vaccination against SARS-CoV-2 for people with a current or past TB disease, as well as rapid diagnosis and targeted treatment of TB in highly specialized pulmonology institutions, presents key points to avoid excessive morbidity and mortality.